Determinants of child labor in Tanzania: a BGEE model analysis of the ILFS 2020/2021 - Hebron A. Mtafya; Srinivasa Rao Gadde; Jairos K. Shinzeh (Cogent Social Sciences)
In Tanzania, millions of children continue to engage in hazardous, exploitative jobs, making it difficult for them to receive an education and enjoy a safe upbringing. This study aims to identify the major variables that affect child labor in Tanzania using data from the Integrated Labour Force Survey 2020/2021. Unweighted binary generalized estimating equation models are used in the study to evaluate the individual, family, and social factors that influence the participation of children in labor. The results show that key influences on child labor in Tanzania include household head education, head of household marital status, family size, location, child age, and household with an employed member. For stakeholders and policymakers creating focused programs and policies to prevent child labor and enhance children’s rights to education and a brighter future, the results provide important information. By being able to account for within-cluster correlations and generate population average values, this model’s use is justified and makes it possible to fully analyze the variables impacting child labor. By comprehending the root causes of child labor, Tanzania may develop evidence-based policies and programs that prioritize children’s health, education, and safety from dangerous jobs. Tanzania would be able to break the cycle of exploitation and poverty that encourages child labor.